ON THE QUESTION OF THE NECESSITY OF NORMATING BIO-TRANSFORMED SUBSTANCES MEDICINAL PREPARATIONS IN OBJECTS OF THE ENVIRONMENT (SHORT MESSAGE) - Ibragimova N.A.,; Lyu М.B,; Dr. Snow Daniel D.,; Sabitov А.N, (Academic Journal of Physical and Chemical Sciences, 2019)
After entering the body, medications are subjected to a cascade of interrelated biochemical reactions, which result in not only is the pharmacological effect achieved, but also the formation of the biotransformation products. Theses chemicals ultimately wind up in waste water, where they are also exposed a whole complex of abiotic and biotic processes. As a result, chemical compounds with new properties can be formed, able to change physiological, biochemical, genetic and other parameters living organisms and to enter the food chain into the human body. Therefore, it can be argued about the urgent problem on the necessity of predicting and understanding biotransformed products of medicinal products in environmental objects, and including wastewater, which will determine the impact of the risks health risks, expand (supplement) the standards of environmental pollution and define a strategy for finding and developing new drugs.